Design Simulation Program of Runway Capacity Using Genetic Algorithm at Soekarno-Hatta - Hoga Saragih; Indra Sulistyo Wibowo; Wisnu Darjono Tulodo Utomo; Rusdianto Roestam (Institute of Advanced Engineering and Science, 2011)
The purposes of this research are to calculate the capacity of runway with runway capacity simulation software using Genetic Algorithm, and to analyze the efforts which have more profound effect. To enhance the runway capacity, some strategies are researched, such as reduction of separation to meet criteria set by FAA’s rule, addition of the exit taxiway, addition of the runway according to master plan of Soekamo-Hatta Airport and changing the runway utilization strategies. Out of the four strategies, the most efficient solution is changing the runway utilization strategies and reduction in separation. However, the addition of runway has the highest capacity increase. Keywords: genetic algorithm, simulation, runway capacity.DOI:http://dx.doi.org/10.11591/ijece.v1i2.85